<meta http-equiv="refresh" content="1; url=/nojavascript/"> Deriving and Using the Quadratic Formula | CK-12 Foundation
Skip Navigation
You are reading an older version of this FlexBook® textbook: CK-12 Algebra II with Trigonometry Concepts Go to the latest version.

5.13: Deriving and Using the Quadratic Formula

Difficulty Level: At Grade Created by: CK-12
Practice Quadratic Formula
Practice Now

The profit on your school fundraiser is represented by the quadratic expression -3p^2 + 200p - 3000 , where p is your price point. What is your break-even point (i.e., the price point at which you will begin to make a profit)? Hint: Set the equation equal to zero.

Watch This

Khan Academy: Quadratic Formula 1


The last way to solve a quadratic equation is the Quadratic Formula. This formula is derived from completing the square for the equation ax^2+bx+c=0 (see #13 from the Problem Set in the previous concept). We will derive the formula here.

Investigation: Deriving the Quadratic Formula

Walk through each step of completing the square of ax^2+bx+c=0 .

1. Move the constant to the right side of the equation. ax^2+bx=-c

2. “Take out” a from everything on the left side of the equation. a\left(x^2+\frac{b}{a}x\right)=-c

3. Complete the square using \frac{b}{a} . \left(\frac{b}{2}\right)^2=\left(\frac{b}{2a}\right)^2=\frac{b^2}{4a^2}

4. Add this number to both sides. Don’t forget on the right side, you need to multiply it by a (to account for the a outside the parenthesis). a\left(x^2+\frac{b}{a}x+\frac{b^2}{4a^2}\right)=-c+\frac{b^2}{4a}

5. Factor the quadratic equation inside the parenthesis and give the right hand side a common denominator. a\left(x+\frac{b}{2a}\right)^2=\frac{b^2-4ac}{4a}

6. Divide both sides by a . \left(x+\frac{b}{2a}\right)^2=\frac{b^2-4ac}{4a^2}

7. Take the square root of both sides. x+\frac{b}{2a}=\pm \frac{\sqrt{b^2-4ac}}{2a}

8. Subtract \frac{b}{2a} from both sides to get x by itself. x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}

This formula will enable you to solve any quadratic equation as long as you know a, b , and c (from ax^2+bx+c=0 ).

Example A

Solve 9x^2-30x+26=0 using the Quadratic Formula.

Solution: First, make sure one side of the equation is zero. Then, find a, b, and c . a = 9, b = -30, c = 26 . Now, plug in the values into the formula and solve for x .

x &=\frac{-(-30)\pm \sqrt{(-30)^2-4(9)(26)}}{2(9)}\\&=\frac{30\pm \sqrt{900-936}}{18}\\&=\frac{30\pm \sqrt{-36}}{18}\\&=\frac{30\pm 6i}{18}\\&=\frac{5}{3} \pm \frac{1}{3}i

Example B

Solve 2x^2+5x-15=-x^2+7x+2 using the Quadratic Formula.

Solution: Let’s get everything onto the left side of the equation.

2x^2+5x-15 &=-x^2+7x+2\\3x^2-2x-17 &=0

Now, use a = 3, b = -2, and c = -17 and plug them into the Quadratic Formula.

x &=\frac{-(-2) \pm \sqrt{(-2)^2-4(3)(-17)}}{2(3)}\\&=\frac{2 \pm \sqrt{4+204}}{6}\\&=\frac{2 \pm \sqrt{208}}{6}\\&=\frac{2 \pm 4\sqrt{13}}{6}\\&=\frac{1 \pm 2\sqrt{13}}{3}

Example C

Solve x^2+20x+51=0 by factoring, completing the square, and the Quadratic Formula.

Solution: While it might not look like it, 51 is not a prime number. Its factors are 17 and 3, which add up to 20.

x^2+20x+51 &=0\\(x+17)(x+13) &=0\\x &=-17, -3

Now, solve by completing the square.

x^2+20x+51 &=0\\x^2+20x &=-51\\x^2+20x+100 &=-51+100\\(x+10)^2 &=49\\x+10 &=\pm 7\\x &=-10 \pm 7 \rightarrow -17, -3

Lastly, let’s use the Quadratic Formula. a = 1, b = 20, c = 51 .

x &=\frac{-20 \pm \sqrt{20^2-4(1)(51)}}{2(1)}\\&=\frac{-20 \pm \sqrt{400-204}}{2}\\&=\frac{-20 \pm \sqrt{196}}{2}\\&=\frac{-20 \pm 14}{2}\\&=-17, -3

Notice that no matter how you solve this, or any, quadratic equation, the answer will always be the same.

Intro Problem Revisit The break-even point is the point at which the equation equals zero. So use the Quadratic Formula to solve -3p^2 + 200p - 3000 for p .

-3p^2 + 200p - 3000 = 0

Now, use a = -3, b = 200, and c = -3000 and plug them into the Quadratic Formula.

p &=\frac{-(200) \pm \sqrt{(200)^2-4(-3)(-3000)}}{2(-3)}\\&=\frac{-200\pm \sqrt{40000-36000}}{-6}\\&=\frac{-200\pm \sqrt{4000}}{-6}\\&=\frac{-200\pm 20\sqrt{10}}{-6}\\&=\frac{100}{3} \pm \frac{10\sqrt{10}}{3}

Therefore, there are two break-even points: \frac{100}{3} \pm \frac{10\sqrt{10}}{3} .

Guided Practice

1. Solve -6x^2+15x-22=0 using the Quadratic Formula.

2. Solve 2x^2-x-15=0 using all three methods.


1. a = -6, b = 15, and c = -22

x &=\frac{-15 \pm \sqrt{15^2-4(-6)(-22)}}{2(-6)}\\&=\frac{-15 \pm \sqrt{225-528}}{-12}\\&=\frac{-15 \pm i \sqrt{303}}{-12}\\&=\frac{5}{4} \pm \frac{\sqrt{303}}{12}i

2. Factoring : ac = -30 . The factors of -30 that add up to -1 are -6 and 5. Expand the x- term.

2x^2-6x+5x-15 &=0\\2x(x-3)+5(x-3) &=0\\(x-3)(2x+5) &=0\\x &=3, -\frac{5}{2}

Complete the square

2x^2-x-15 &=0\\2x^2-x &=15\\2\left(x^2-\frac{1}{2}x\right) &=15\\2\left(x^2-\frac{1}{2}x+\frac{1}{16}\right) &=15+\frac{1}{8}\\2\left(x-\frac{1}{4}\right)^2 &=\frac{121}{8}\\\left(x-\frac{1}{4}\right)^2 &=\frac{121}{16}\\x-\frac{1}{4} &= \pm \frac{11}{4}\\x &=\frac{1}{4} \pm \frac{11}{4} \rightarrow 3, -\frac{5}{2}

Quadratic Formula

x &=\frac{1 \pm \sqrt{1^2-4(2)(-15)}}{2(2)}\\&=\frac{1 \pm \sqrt{1+120}}{4}\\&=\frac{1 \pm \sqrt{121}}{4}\\&=\frac{1 \pm 11}{4}\\&=\frac{12}{4}, -\frac{10}{4} \rightarrow3, -\frac{5}{2}

Explore More

Solve the following equations using the Quadratic Formula.

  1. x^2+8x+9=0
  2. 4x^2-13x-12=0
  3. -2x^2+x+5=0
  4. 7x^2-11x+12=0
  5. 3x^2+4x+5=0
  6. x^2-14x+49=0

Choose any method to solve the equations below.

  1. x^2+5x-150=0
  2. 8x^2-2x-3=0
  3. -5x^2+18x-24=0
  4. 10x^2+x-2=0
  5. x^2-16x+4=0
  6. 9x^2-196=0

Solve the following equations using all three methods.

  1. 4x^2+20x+25=0
  2. x^2-18x-63=0
  3. Writing Explain when you would use the different methods to solve different types of equations. Would the type of answer (real or imaginary) help you decide which method to use? Which method do you think is the easiest?

Image Attributions


Difficulty Level:

At Grade


Date Created:

Mar 12, 2013

Last Modified:

Feb 26, 2015
Files can only be attached to the latest version of Modality


Please wait...
Please wait...
Image Detail
Sizes: Medium | Original

Original text